2015
DOI: 10.7196/samj.8785
|View full text |Cite
|
Sign up to set email alerts
|

Oral v. pulse intravenous cyclophosphamide: A retrospective analysis of adverse events in a setting with a high burden of infectious disease

Abstract: Background. Cyclophosphamide (CPM) is still considered to be the first-line treatment for many life-threatening autoimmune conditions. It does, however, carry a significant risk of serious adverse events, especially infections. At present CPM is administered as either a daily oral dose (DOC) or an intravenous pulse (PIVC). There is uncertainty regarding the safety profiles of both regimens in settings with a high burden of infectious diseases. Objective. To compare the frequency and nature of adverse events re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…All the previous studies also demonstrated that intravenous pulse cyclophosphamide therapy was associated with lower adverse events compared to oral cyclophosphamide. 15,16 It is also possible that proper hydration of the patient during the pulse therapy reduced adverse events.…”
Section: Resultsmentioning
confidence: 99%
“…All the previous studies also demonstrated that intravenous pulse cyclophosphamide therapy was associated with lower adverse events compared to oral cyclophosphamide. 15,16 It is also possible that proper hydration of the patient during the pulse therapy reduced adverse events.…”
Section: Resultsmentioning
confidence: 99%
“…The oral Cyclophosphamide regimen is not favoured because it is associated with longer treatment duration, greater cumulative doses and more severe leucopenia. 41 • The Euro Lupus regimen which uses less doses of cyclophosphamide is not favoured in Africa where the disease is much more severe compared to the population in the Euro Lupus study. 10,29,42 All regimens IV Methylprednisolone in severe cases followed by oral prednisolone 0.5-1mg/kg tapered over 6 to 12 months according to clinical response…”
Section: Immunosuppressive Treatmentmentioning
confidence: 98%